Workshop on fisheries management in rural reservoirs : (The Mekong Secretariat, 1995)
This report aims to summarize the experience from reservoir fisheries management in Thailand and this workshop may be another step forward in an increased cooperation on fisheries research and development in the Mekong Basin.